Perbedaan Pola Asuh Ayah dan Ibu, Stres Pengasuhan, dan Faktor Risiko Pola Asuh terhadap Anak Usia Sekolah di Wilayah Pesisir Jakarta: Perbedaan Pola Asuh Ayah dan Ibu, Stres Pengasuhan, dan Faktor Risiko Pola Asuh terhadap Anak Usia Sekolah di Wilayah Pesisir Jakarta - Dwi Hastuti; Dhia Nur Shabrina; Bekti Amalia Faron; Fannisa Septariana; Nur Islamiah (Jurnal Ilmu Keluarga dan Konsumen, 2025)
Parenting is a fundamental aspect that plays a crucial role in a child's development, but in practice, various factors influence the quality of parenting. Accordingly, the objective of this study was to analyze the factors that affect parenting practice and parenting stress between father and mother. This study employed a quantitative method utilizing a cross-sectional research design. There were 99 pairs of parents (99 fathers and 99 mothers) with children aged 9-12 years involved who had been selected using convenient sampling method . The respondents were guided to fill-in questionnaire using a structured instrument. The data were analyzed with different t-test and correlation test.The findings revealed that half of fathers and mothers have applied parenting practice properly and majority of them experienced very low level of parenting stress. There were no significant differences in parenting practices between father and mother. However mother tend to practice asih better, while father  practice asah and asuh more higher than mother.  Different result was reported for pleasure dimension in parenting stress. Correlation test discovered that higher mother education will increase parenting quality of mother. Meanwhile, working mother and mother with higher income were associated with decreasing level of stress dimension.